Growth and yield of peanut on peat soil with different dolomite and shrimp waste liquid organic fertilizer (LOF) levels - Ongki Aleksa Samson; Mahmudi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
The application of dolomite and shrimp waste liquid organic fertilizer (LOF) is expected to improve the quality of peat soil to support the growth and yield of peanuts. The study was aimed at the role of dolomite and shrimp waste LOF in the development and yield of peanuts on peat soil. The study was conducted in Kubu Raya Regency, West Kalimantan, from April to August 2024. A factorial completely randomized design was used for the field experiment. The treatment factors were the dosage of dolomite (3, 6, and 9 tons ha-1) and the concentration of shrimp waste LOF (200, 300, and 400 mL L-1). The results showed that using dolomite and shrimp waste LOF increased the growth and yield of peanuts on peat soil. The interaction of dolomite 6 tons ha-1 and shrimp waste LOF 400 mL L-1 effectively increased root volume. The best individual dolomite treatment level for peanut growth was 6 tons ha-1, and for production, it was 9 tons ha-1. The best individual shrimp waste LOF treatment level for growth was 300 mL L-1, and for production, it was 400 mL L-1. Keywords: amelioration; peanut production; soil fertility